First molecular detection of co-infection of honey bee viruses in asymptomatic Bombus atratus in South America - Reynaldi, Francisco José (2013)
Pollination is critical for food production and has the particularity of linking natural ecosystems with agricultural production systems. Recently, losses of bumblebee species have been reported worldwide. In this study, samples from a commercial exploitation of bumblebees of Argentina with a recent history of deaths were studied using a multiplex PCR for the detection of the honey bee viruses most frequently detected in South America. All samples analyzed were positive for co-infections with Deformed Wing Virus, Black Queen Cell Virus and Sacbrood virus. This is the first report of infection of Bombus atratus with honey bee viruses. A better understanding of viral infections in bumblebees and of the epidemiology of viruses could be of great importance as bumblebees can serve as possible viral reservoirs, resulting in pathogen spillover towards honey bees and native bumblebees.